2014
DOI: 10.1016/j.jor.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomyogenic (Epithelioid sarcoma-like) hemangioendothelioma with bone invasion

Abstract: To the best of our knowledge is the first case report of epithelioid sarcoma-like hemangioendothelioma with bone invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…As for keratins, AE1/AE3 was focally but not diffusely positive in this case. AE1/AE3 was usually positive in cases of pseudomyogenic hemangioendothelioma reported so far [ 1 – 5 , 10 14 ]. Some documents mentioned that the immunostaining pattern is diffuse.…”
Section: Discussionmentioning
confidence: 99%
“…As for keratins, AE1/AE3 was focally but not diffusely positive in this case. AE1/AE3 was usually positive in cases of pseudomyogenic hemangioendothelioma reported so far [ 1 – 5 , 10 14 ]. Some documents mentioned that the immunostaining pattern is diffuse.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment for PHE remains surgical excision of the lesions, even when there are multiple lesions, and sometimes amputation is needed to control the disease (2,3,6,7,11,15). Related to the characteristic SERPINE1-FOSB fusion of PHE, IJzendoorn et al recently reported the durable, complete remission of a patient with advanced unresectable PHE treated with telatinib (16).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is little literature regarding ES-H of bone. Primary bone lesions may be aggressive, with cortical destruction and soft tissue invasion (Karakasli et al 2014 ; Xu et al 2012 ). ES-H in our study showed cortical destruction, marked cystic/necrotic component, and abnormally enhanced tumor tissue, which was suggestive of malignant vascular tumor of bone.…”
Section: Discussionmentioning
confidence: 99%